Analysis Of Down Passing Skills In Games Volleyball - Wendi Sahputra; Supriyanto Supriyanto; Mariska Febrianti (Hanoman Journal: Physical Education and Sport, 2021)
This study aims to determine the skills of students in doing Passing Under Volleyball in Class VI students at SD Negeri 112 Seluma Regency. The method used in this research is descriptive quantitative which is carried out to determine the value of independent variables, either one or more (independent) variables without making comparisons or connecting with other variables. The population in this study were students who were in class VI SD Negeri 112 Seluma. Sampling in this study using total sampling, because the entire population was used as a sample of 32 students. The data analysis technique used is percentage. From the results of data analysis, description, testing of research results, and discussion, it can be concluded that the passing ability of Class VI students at SD Negeri 112 Seluma is at the level of qualification in the "good" category of 56.25 % (18 students), the "medium" category was 34.37% (11 students), and the "poor" category was 9.38% (3 students). So that it can be concluded that most of the Class VI students at SD Negeri 112 Seluma have been able to do underhand passes well.